(untitled) (Intent Research Scientific Journal, 2026)
In the 1899 novel Heart of Darkness, Joseph Conrad writes a seminal work of early modernism, which is dealing with the complexities of human nature and the moral ambiguities of European colonialism. The story tells of a seasoned sailor called Charles Marlow, who sets off up the Congo River to find the enigmatic Kurtz, and it critiques the brutal realities that colonization introduces as well as questions the ethical foundation for imperialism. Conrad uses Marlow’s experience in the novella as a platform to symbolize the vain and corrupt morality that Europeans attribute to their so-called "civilizing mission". Taking place amidst the Scramble for Africa, the novella explores the destructive impact of colonialism on both the colonizer and the colonized. Conrad humanizes his European characters with the very presentation of moral disintegration and the dehumanization of the African people as strong allegory, which questioned the moral premise upon which colonial projects were justified. Further, the themes of moral ambiguity and darkness in humanity are highlighted by the narrative techniques of the novella, which include unreliable narration and symbolic imagery. Much more than that, Heart of Darkness is an evocative indictment against imperialism and a deep exploration of human fate: it conjures readers to confront the ethical problems and complexities of colonial exploitation.